A Myc–microRNA network promotes exit from quiescence by suppressing the interferon response and cell-cycle arrest genes - Polioudakis, Damon; Bhinge, Akshay A.; Killion, Patrick J.; Lee, Bum-Kyu; Abell, Nathan S.; Iyer, Vishwanath R. (Nucleic acids research, 2013)
The transition of mammalian cells from quiescence to proliferation is accompanied by the differential expression of several microRNAs (miRNAs) and transcription factors. However, the interplay between transcription factors and miRNAs in modulating gene regulatory networks involved in human cell proliferation is largely unknown. Here we show that the miRNA miR-22 promotes proliferation in primary human cells, and through a combination of Argonaute-2 immunoprecipitation and reporter assays, we identified multiple novel targets of miR-22, including several cell-cycle arrest genes that mediate the effects of the tumor-suppressor p53. In addition, we found that miR-22 suppresses interferon gene expression by directly targeting high mobility group box-1 and interferon regulatory factor (IRF)-5, preventing activation of IRF3 and NF-κB, which are activators of interferon genes. The expression of interferon genes is elevated in quiescent cells and their expression is inhibitory for cell proliferation. In addition, we find that miR-22 is activated by the transcription factor Myc when quiescent cells enter proliferation and that miR-22 inhibits the Myc transcriptional repressor MXD4, mediating a feed-forward loop to elevate Myc expression levels. Our results implicate miR-22 in downregulating the anti-proliferative p53 and interferon pathways and reveal a new transcription factor-miRNA network that regulates the transition of primary human cells from quiescence to proliferation.